PERANCANGAN SISTEM PAKAR BERBASIS WEB UNTUK DIAGNOSIS KERUSAKAN LAPTOP MENGGUNAKAN METODE FORWARD CHAINING - lulu; lulu julia julia; Dahlan; Syarifuddin (Rabit : Jurnal Teknologi dan Sistem Informasi Univrab, 2026)
Laptop hardware failures are often difficult for users to identify due to limited knowledge of their symptoms and types. This condition often forces users to rely on technicians for an initial diagnosis. This study aims to develop a web-based expert system for diagnosing laptop hardware failures using the Forward Chaining method. The system was developed using the Waterfall model within the System Development Life Cycle (SDLC) framework and implemented using the CodeIgniter 4 (CI4) framework with a MySQL database. Knowledge acquisition was conducted through literature review, observation, and interviews with laptop technicians, and the acquired knowledge was represented as IF–THEN rules within the system's knowledge base. System functionality was evaluated using the Black Box Testing method, while diagnostic validation was performed by comparing the system's diagnosis with the diagnosis provided by expert technicians using 21 test cases. The results showed that all system functions operated as designed, and the validation demonstrated agreement between the system's diagnosis and the expert's diagnosis for the tested cases. These findings indicate that the Forward Chaining method can be effectively applied to support the initial diagnosis of laptop hardware failures through a web-based expert system.